O silêncio de Deus em Morangos Silvestres e O Sétimo Selo de Ingmar Bergman - Sinay, Isadora Goldberg (2014)
The presente dissertation is composed by the analysis of two fiction feature films, Wild Strawberrys and The Seventh Seal, by Ingmar Bergman. The analysis highlights, in both works, the theme of the Silence of God, importante aspect in the work of the filmmaker. Ingmar Bergman is one of the biggest names in contemporary art and his films articulate philosphy and religion, making then a piece of fundamental interest to the Science of Religions as a manifestation of essential reflections in the artistic production of a society. The analysis supports itself in the works of film analysis by Jesse Kalin and Paisley Livingston and focus in understanding the silence of God as a form of abandom and seeing the carachters search for a personal answer from the divinity as a way of conquering meaning and mercy in their lives. As the analysis goes it is verified that this answer can not be found in the transcendency, by exactly when the caracther stop looking in its direction and turns his sight to the concrete and imanent